High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Endophytic fungi mediate litter decomposition dynamics through microbial interactions and temporal shifts - Yuan-Qi Zhao; Fu-Sen Nan; Xiao-Qian Yang; Jian-Fei Yu; Han-Yue Bi; Si-Jun Duan; Xin-Yue Wang; Tian-Ci Chen; Qin-Jiang Mao; Xiao-Bo Wang (Soil Biology and Biochemistry, 2026)

Efficient purification of bio-oil-derived levoglucosenone via a multi-stage synergistic separation strategy - Kai Li; Yong-sheng Ma; Bo Wang; Ding-wang Qiao; Qi Niu; Cheng-long Ruan; Bi-heng Bao; Xin-hua Yuan; Qiang Lu (Biomass and Bioenergy, 2026)

Effect of sugars and non-sugar sweeteners on aroma compound release, sensory quality and physical properties of flat peach puree and derived vacuum-freeze-dried products - Liya Liu; Lichang Yan; Yu Zhang; Jihong Wu; Xin Pan; Bo Cai; Shuang Bi; Ye Liu (Food Research International, 2026)

Antibacterial mechanism and preservation effect of antimicrobial peptide T1 against Listeria monocytogenes in smoked salmon - Bo Bi; Wenxi Xie; Jiaojiao Tan; Zhuming Ye; Zhijie Yang; Puyu Liu; Guo Liu; Xiaoqi Liang; Chi-Tang Ho; Xiaoqing Li; Yong Cao (Food Chemistry, 2026)

Disentangling the role of sheet flow in sediment distribution heterogeneity across micro-topographic sloping farmland - Lin Chen; Ruijie Yang; Bo Bi; Qinqian Meng; Jie Lin; Jian Wang (Soil and Tillage Research, 2026)

Manure-free organic fertilization-derived lignin alters the dissemination of antibiotic resistance genes from soil to the rhizosphere - Bing-Jie Jin; Song-Can Chen; Bi-Xiao Ji; Hai-Bo Wang; Xin-Yuan Li; Yi Zhao; Kai Ding; Gang Li (Environmental Research, 2026)

From semi-quantitative grading to continuous quantification: High-resolution characterization of bioturbation intensity in carbonate cores via deep learning - Jia-Kang He; Bi-Bo Lu; Yong-Bin Niu (Computers & Geosciences, 2026)

Dietary Bacillus sp. ‌Modulates Multi-tissue Metabolism Through Gut Microbiota Remodeling in High-fat Fed Larimichthys crocea - Ruojing Li; Biao Yuan; Xin Yi; Ermei Yin; Bi Huang; Qianwen Min; Jiayu Zhou; Meiqi Lv; Bo Zhang; Na Zhao (Probiotics and Antimicrobial Proteins, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Study on the removal of enrofloxacin from surface water by high sulfur coal/persulfate system - Yaru Zhang; Wenlong Bi; Bo Sun; Fenwu Liu; Shaozu Xu; Yashi Liu; Xinyu Fan; Yuyang Wang (Journal of Environmental Chemical Engineering, 2026)

From morphological constraints to genomic SNPs: Developing population identification methods exemplified by large yellow croaker (Larimichthys crocea) - Zebin Zhou; Xubing Ba; Qianwen Min; Jiayu Zhou; Xin Yi; Ruojing Li; Bi Huang; Na Zhao; Bo Zhang; Songlin Chen (Aquaculture, 2026)

Canonical Wnt pathway mediates catalpol-induced epithelial differentiation of porcine metanephric mesenchymal cells - Pengcheng Ji; Yuansheng Xie; Guangrui Geng; Wenkai Guo; Jingru Bi; Bing Han; Xu Wang; Bo Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Influence of soluble–insoluble rock interfaces on water and mud inrush mechanisms in water-rich tunnels: Insights from CFD–DEM coupled simulations - Zuodong Xie; Chuan He; Ziquan Chen; Bo Wang; Yulin Zou; Jinglong Bi (Tunnelling and Underground Space Technology, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Distinct Dispersal Directions Out of the Qinghai–Tibet Plateau Resulted in Contrasting Evolutionary Trajectories - Yuan‐Yuan Ling; Kun‐Li Xiang; Bi‐Bo Zhang; Huan‐Wen Peng; Andrey S. Erst; Liang Zhao; Tatyana V. Erst; Florian Jabbour; Wei Wang (Journal of Biogeography, 2026)
Aim The Qinghai–Tibet Plateau (QTP) harbours high levels of species diversity and endemism, and multiple out‐of‐QTP dispersal routes have been put forward. However, whether different dispersal directions out of the QTP resulted in contrasting evolutionary trajectories remains unknown. Here, we use the sister genera Calathodes and Trollius (Ranunculaceae) as an ideal model to investigate the out‐of‐QTP diversification patterns. Location The Northern Hemisphere. Taxon Calathodes and Trollius (Ranunculaceae). Methods We sampled all four species of Calathodes and 38 species of Trollius to reconstruct a near‐complete species‐level phylogeny based on 12 molecular loci from the nuclear and plastid genomes. Within the phylogenetic framework, divergence times, ancestral ranges and diversification rates were estimated, and ancestral habitat, elevation and climate niche were inferred. Results The most recent common ancestor of Calathodes and Trollius occupied the QTP at ~8 Ma. Calathodes migrated eastward from the QTP to subtropical mainland China at ~4 Ma and then further to Taiwan at ~0.5 Ma. Trollius dispersed into North Asia at ~6 Ma and further reached Northeast Asia, Japan, Taiwan, Europe and North America. Net diversification rates of subtropical Calathodes and North Asian Trollius clades were 0.28 and 0.54 My −1 , respectively. Calathodes and its subtropical clade both prefer the middle‐elevation closed, warm, and humid habitats, while Trollius and its North Asian clade inhabit open, cold, and dry areas. Main Conclusions Calathodes and Trollius both originated in the QTP in the late Miocene and exhibited long‐term habitat and climatic niche conservatism. The distinct out‐of‐QTP dispersal directions in the two genera probably resulted in their subsequent different diversification patterns, associated with the conservatism in habitat‐ and climate‐related niches. Our study suggests the QTP serves as an important source of Northern Hemisphere biodiversity and advances the knowledge of how distinct dispersal directions out of the QTP resulted in contrasting evolutionary trajectories.

Development of a numerical model to investigate wave-driven dynamics and turbulence in flexible seagrass meadows - Bo Zhang; Guo-Hai Dong; Chun-Wei Bi; Qi-Ying Sun; Shou-An Guo (Ocean Engineering, 2026)

Synergistic coupling of micellar confinement and interfacial adsorption for fabricating high-density spherical nickel (II) tricarbohydrazide perchlorate - Jie-xin He; Dong-xu Zhang; Feng-yi Xia; Ri-lige Su; Bo-bo Lu; Jia-ni Xie; Zi-jie Bi; Qian-you Wang; Li Yang (Chemical Engineering Journal, 2026)

Thermally stable alkaline chitin solutions via cryogenic processing enable homogeneous functionalization - Shichao Bi; Jinchang Liang; Guohui Sun; Jiakui Ren; Xiaoqiang Wang; Bo Tang (Carbohydrate Polymers, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

Immobilization-mediated algae-bacteria interactions improve swine wastewater treatment and microalgal biomass energy conversion: Performance, correlation and microscopic mechanisms - Bo Sun; Xuemei Yao; Zhenye Tong; Hong Yang; Junmei Qin; Wenlong Bi; Xingxing Qiao; Qingjie Hou; Fenwu Liu (Journal of Environmental Management, 2026)

Future temperature-related labour loss due to premature deaths: a multi-country study - Bo Wen; Zanfina Ademi; Yao Wu; Rongbin Xu; Pei Yu; Yanming Liu; Wenhua Yu; Tingting Ye; Wenzhong Huang; Zhengyu Yang; Yiwen Zhang; Yuxi Zhang; et al. (Environmental Research, 2026)

Occurrence, Distribution and Ecological Risk Assessment of Phthalate Esters in Sediments of Poyang Lake and its Tributaries - Yan Ma; Runxuan Li; Qingyuan Liu; Ke Zhang; Jiale Bi; Bo-Tao Zhang; Yan Liu; Peng Shao (Water, Air, & Soil Pollution, 2026)

Effects of light intensity and photoperiod on the growth performance, stress response, and metabolism of steelhead trout (Oncorhynchus mykiss) - Xiao Liu; Liuyi Huang; Qiqing Liu; Run Wang; Bo Liu; Zhaomin Li; Yacai Song; Ziyi Huang; Chunwei Bi; Xinxing You (Aquaculture, 2026)

Effects of metals on thermal oxidation of jet fuel and mitigation strategies - Bowang Lu; Xiaoyong Fan; Dong Li; Jun Yang; Long Yan; Bo Yang; Guanghui Pang; Jian Li; Bi Chen (Fuel, 2026)

A novel antimicrobial peptide FxCy2 against Helicobacter pylori: Isolation and purification from Lactobacillus paracasei FX-6 - Bo Bi; Meng Kang; Qianru Lin; Qun Wang; Xiaoqing Li; Zhuming Ye; Chi-Tang Ho; Yong Cao (Food Research International, 2026)

Discrimination of seismic event near the North Korean nuclear test site (January-March 2022) using multi-station P/S spectral ratios - Bo-Han Wang; Lian-Feng Zhao; Xiao-Bi Xie; Xi He; Yong Zhao; Zhen-Xing Yao (Journal of Seismology, 2026)

Combined with wavelet time frequency analysis and lightweight deep convolutional networkintelligent recognition of coal rock acoustic emission signal - Zhong-kai Peng; Wei-jian Liu; Zhi-zeng Zhang; Zhen-xia Yuan; Shi-lei Zhen; Zhuang-zhuang Wang; Xin-bo Luan; Jian-bo Li; Hao-yang Li; Bi-qi Yuan; Shuai Teng; Zi-wei Li (Applied Geophysics, 2026)

Long-term remote sensing reveals the development of informal settlements and their impact on land surface temperature in African drylands: A case study of Windhoek, Namibia - Zilong Xia; Nan Jia; Bo Yuan; Ruishan Chen; Haowei Mu; Mo Bi; Uchendu Eugene Chigbu; Penghui Jiang (Sustainable Cities and Society, 2026)

Wave field characteristics around an integrated net cage based on a monopile wind turbine foundation as determined by CFD model - Shou-An Guo; Guo-Hai Dong; Chun-Wei Bi; Bo Zhang (Ocean Engineering, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Experimental study on the effect of air-conditioning system on smoke and temperature in metro carriage fires - Lingwei Feng; Yuanlong Zhou; Haiquan Bi; Huajin Zhang; Yong Sun; Jing Wang; Bo Lei (Tunnelling and Underground Space Technology, 2025)

Two new compounds from the roots of Mirabilis jalapa L. and their cytotoxic activity in vitro - Xiao-Mei Yan; Tian-Tian Qu; Jie Luan; Hou-Run Zhang; Xiang-Qin Tang; Xiao-Xu Bi; Ying Wang; Bing Chen; Jiang-Bo He (Phytochemistry Letters, 2025)

The response of non-point source pollution to land use changes based on the SWAT and PLUS models in an agricultural river basin of Yangtze River, China - Yiqing Bi; Depeng Zuo; Yonghui Song; Zongxue Xu; Jing Wang; Dingzhi Peng; Bo Pang; Wenchao Sun; Karim C. Abbaspour; Hong Yang (Journal of Hydrology, 2025)

Experimental Study on the Structural Dynamic Response of an Offshore Electrical Platform During Mating Process in Float-Over Installation - Yinfeng Wang; Bo Zhang; Zongjun Shan; Zhenzhou Sun; Jiefeng Chen; Xu Jiang; Guohai Dong; Chunwei Bi (Journal of Marine Science and Engineering, 2025)
As offshore wind power moves into deeper waters, large-scale electrical platforms are key to efficient power transmission. However, their heavy topside modules create major installation challenges. As traditional lifting methods are inadequate, the float-over method has become a viable solution for installing topside modules, but it is essential to study the structural responses to collisions during the process to ensure construction and equipment safety. This study establishes a physical model of the offshore converter station at a 1:65 scale based on the elastic force-gravity similarity principle. Assuming the barge carrying the topside module descends at a constant speed, the study investigates the dynamic response of the platform during the float-over mating process. Float-over collision tests are conducted to obtain the platform’s acceleration, strain, and displacement responses and to analyze the effects of collision speed, offset position, and Leg Mating Unit (LMU) stiffness on the dynamic structural response characteristics. The results show that as collision speed increases from 10 mm/s to 50 mm/s, the topside acceleration response increases up to 5.7 times. Beam strain remains mostly unchanged, and displacement increases first, then decreases. Under fixed descent velocity, x-offset increases jacket strain and converter valve acceleration, while y-offset raises platform acceleration and reduces valve acceleration by approximately 20 percent. At 50 mm/s, higher LMU stiffness causes the acceleration response to first drop, then rise. These findings support safe float-over installation.

Asynchronous storming-norming ant colony system for project scheduling under scenario perturbation of activity attributes - Wen Shi; Feng-Feng Wei; Xiaolin Bo; Zhisheng Bi; Jianing Xi; Wei-Neng Chen (Swarm and Evolutionary Computation, 2025)

Effect of nutrient addition and mowing on plant diversity and soil carbon content of meadow steppe in Inner Mongolia - Huayi Zhang; Chenxu Liu; Jiling Tan; Weiheng Bi; Xuefeng Chen; Bo Bai; Namuhan; Wuyunna; Guangdi Li; Yantao Song (Journal of Environmental Management, 2025)

Oxidative polymerization of PEDOT in YMOF-NH2 framework for electrochemically controlled phosphate removal and enrichment - Zhuangzhuang Bi; Zhangjie Huang; Guang Li; Yuanyuan Guo; Qing Qu; Bo Wu (Journal of Environmental Chemical Engineering, 2025)

Emerging role of RNA m6A modifications in laryngeal squamous cell carcinoma: insights into tumorigenesis and therapeutic potential - Guotong Zheng; Jing Bi; Yangyan Yan; Bo Yu; Yong Fu (Apoptosis, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Ga- and Ge-bearing minerals and trace element-rich magnetite in the Makeng skarn Fe polymetallic deposit, Eastern China - Xiang-Xue Weng; Yu-Miao Meng; Xiao-Wen Huang; Lin-Bo Shang; Rui-Zhong Hu; Xian-Wu Bi (Journal of Asian Earth Sciences, 2025)

Recombinant canine distemper virus expressing virus-like particle VP2 protein of mink enteritis virus protects minks against lethal challenges of both viruses - Yuan Jiang; Yiyang Sun; Boyu Zhai; Tianjie Chen; Yang Li; Lina Ren; Yuchen Ma; Kun Han; Jianke Wang; Zhenwei Bi; Bo Hu; Jianjun Zhao (Veterinary Microbiology, 2025)

Evaluation of ensiled protein grass as a novel feed ingredient in diets for lambs: Effects on fattening performance, meat quality and flavor - Yanmei Zhang; Chunxu Yang; Bo Chen; Wei Zhou; Naifeng Zhang; Yan Tu; Qiyu Diao; Tao Ma; Huaisen Chen; Kai Chen; Mahmoud M. Abdelsattar; Yanliang Bi (Food Chemistry, 2025)

Improving electrochemical performance of silicon-carbon anode for lithium-ion batteries via one-step etching - Huai-Min Wang; Ying Zhou; Bi-Rong Luo; De-Jun Li; Bo Zhang (Chemical Engineering Journal, 2025)

Exploring mechanisms of radiation-induced myocardial fibrosis using HMGB1 neutralizing antibody - Gang Wang; Bi-Bo Wu; Sha-Sha Zhao; Jing Zhang; Yu Wang; Yin-Xiang Hu; Jun Wan; Bing Lu; Sheng-Fa Su (Journal of Molecular Histology, 2025)

Cloning and characterization of one novel PR1 gene from Coptis chinensis responding to southern blight - Ran Xu; Xiaohan Li; Yue Ming; Bo Wang; Kai Bi; Limei Wang; Hongxun Wang; Wenjun Zhu; Jingmao You (Physiological and Molecular Plant Pathology, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Re-understanding Sedimentary Characteristics of Shallow-water Delta in Funing Formation, Gaoyou Sag, Subei Basin, Eastern China - Zi-yi Yang; Gui-yu Dong; Lian-bo Zeng; Tian-zhuo Bi; Yong-feng Qiu; Hao Li; Xu Yang; Wen-long Qian; Mehdi Ostadhassan (Applied Geophysics, 2025)

Oxygen/sulfate radicals-generating CaS2O8 nanosonosensitizers induce PANoptosis and calcium overload for enhanced peritoneal metastasis immunotherapy - Qiang Wang; Yingfei Wen; Bo Bi; Kuan Li; Yuanqi Liu; Binbin Li; Shangbo Zhou; Zihang Li; Jiaqi Xu; Miaojuan Qiu; You Li; Meiying Wu; et al. (Science Bulletin, 2025)

ZCCHC3 inhibits PEDV proliferation by degrading nuclear coat proteins via the proteasome pathway - Zuyao Zhang; Shuangyang Wang; Huihui Sun; Jie Li; Jun Wang; Yangfan Li; Haichen Lin; Xuan Wang; Ruimin Bi; Zongyi Bo; Haixiao Shen; Liang Li; et al. (Veterinary Microbiology, 2025)

miR-107 suppresses porcine granulosa cell proliferation and estradiol synthesis while promoting apoptosis via targeting PTGS2 - Shuhan Liu; Jiahao Chen; Mingzheng Liu; Chunlei Zhang; Xiaohuan Chao; Huan Yang; Tianshuo Wang; Hongwei Bi; Yuan Ding; Ziming Wang; Asim Muhammad; Mubashir Muhammad; et al. (Theriogenology, 2025)

Offspring number and composition influence parental care strategy and offspring survival in the azure-winged magpie - Bi-Yun Jia; Zhen-Qin Zhu; Wen-Jing Zhu; Yu-Jie Wang; Ning-Ning Sun; Bo Du (Animal Behaviour, 2025)

Photocatalytic activation of peroxymonocarbonate with a TiO2 catalyst for water remediation - Zihan Shen; Xiuru Bi; Liang Jian; Yiqian Jiang; Zihan Yang; Zhen Li; Bo Li; Peiqing Zhao; Xu Meng (Journal of Environmental Management, 2025)

New insight into the role of bisphenol A on the anammox system: Oxidative stress and quorum sensing mechanisms - Yu Tian; Lingjie Liu; Chunsheng Qiu; Dong Wang; Rui Zhang; Yanmeng Bi; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2025)

Comprehensive upcycling waste siloxane liquid into H2-enriched syngas and silicon carbide via a tandem thermochemical process - Huiyang Bi; Bo Wu; Mingyue Yan; Chen Sun; Zhongjian Li; Yang Hou; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

A novel win–win wastewater treatment process: Recover functional element from sludge to enhances TiO2 for deep photocatalytic oxidation - Bo Sun; Yu Tian; Menglin Feng; Sihan Zhang; Hong Yang; Junmei Qin; Wenlong Bi; Xingxing Qiao; Fenwu Liu; Qingjie Hou (Chemical Engineering Journal, 2025)

Regulating the macroscopic and microscopic self-assembly behavior of hydroxybutyl chitosan based on alkyl distribution - Shichao Bi; Guohui Sun; Tianrui Wang; Di Qin; Qiang Yu; Xiao Ma; Houxi Li; Xiguang Chen; Bo Tang (Carbohydrate Polymers, 2025)

Berbamine inhibits Pseudorabies virus in vitro and in vivo - Liang Li; Muze Lv; Yangfan Li; Huihui Sun; Jie Li; Wenyan Li; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jun Wang; et al. (Veterinary Microbiology, 2025)

Identification of the Shuanglongtan tectonic mélange (ca. 1.7–1.5 Ga) in the southwestern Yangtze Block and it’s tectonic implications - Jun-Ping Liu; Zai-Bo Sun; Xiao-Hu He; Jiang-Tai Zhao; Shi-Jun He; Ling-Jing Bi; Wei-Ke Li (Precambrian Research, 2025)

Cross‐Continental Shifts of Ecological Strategy in a Global Plant Invader - Ramona E. Irimia; Weihan Zhao; Peipei Cao; Madalin Parepa; Zhi‐Yong Liao; Shengyu Wang; Jeannie M. Mounger; Conner Richardson; Fatima Elkott; Xin Zhuang; Jingwen Bi; Jieren Jin; et al. (Global Ecology and Biogeography, 2025)
Aim Plant invasions are a global problem that requires studying plants and their environmental associations across native and introduced ranges. Location 2000 km transects in China, Europe and North America. Time Period June 2019–July 2020. Major Taxa Studied Japanese knotweed ( Reynoutria japonica ). Methods We surveyed 150 populations of Japanese knotweed, a noxious invader of the temperate zone, along 2000 km transects in native China and the introduced ranges of Europe and North America. Results We found that larger plants and denser populations in the introduced ranges were associated with shifts in leaf economy and chemical defences. Introduced knotweed populations had higher SLA but reduced leaf chlorophyll, lignin, C:N ratio and leaf toughness along with altered leaf tannins, flavonoids and alkaloids. We found three distinct multivariate knotweed phenotypes primarily in the introduced ranges, and two multivariate knotweed phenotypes mainly in native populations. Main Conclusions Decreased herbivore and pathogen impacts in introduced populations and changes in environmental associations indicate that enemy release and novel habitat conditions might have driven the emergence of novel ecological strategies in this global plant invader.

Agricultural resource management strategies for greenhouse gas mitigation: The land-energy-food-waste nexus based on system dynamics model - Bo Yu; Xueqing Liu; Xuehao Bi; Hua Sun; Jeroen Buysse (Environmental Impact Assessment Review, 2025)

Effects of protein grass hay as alternative feed resource on lamb's fattening performance and meat quality - Yanmei Zhang; Ruicong Ma; Bo Chen; Wei Zhou; Naifeng Zhang; Yan Tu; Qiyu Diao; Tao Ma; Huaisen Chen; Kai Chen; Hong Ma; Yajuan Guo; et al. (Meat Science, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Berbamine inhibits porcine epidemic diarrhea virus in vitro and in vivo - Hongwei Xiang; Jixue Qiao; Haicheng Lin; Jie Li; Yangfan Li; Huihui Sun; Xuan Wang; Ruimin Bi; Zuyao Zhang; Zongyi Bo; Haixiao Shen; Jinchi Zhou; et al. (Veterinary Microbiology, 2024)

The associations of cold spells with human mortality in Shanghai, China - Shan Jin; Xing Bi; Caiyan Wu; Bo Fang; Qi Li; Chunfang Wang; Conghe Song; Junxiang Li (Urban Climate, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Exploring the application and decision optimization of climate-smart agriculture within land-energy-food-waste nexus - Bo Yu; Xuehao Bi; Xueqing Liu; Hua Sun; Jeroen Buysse (Sustainable Production and Consumption, 2024)

Advanced soft-sensing techniques for predicting furnace temperature in industrial organic waste gasification - Mingyue Yan; Huiyang Bi; HuanXu Wang; Caicai Xu; Lihao Chen; Lei Zhang; Shuangwei Chen; Xuming Xu; Qi Chen; Yingna Jia; Bo Wu; Zhongjian Li; et al. (Process Safety and Environmental Protection, 2024)

Bio-refinery of organic pollutants for wastewater reclamation - Haifeng Zhang; Yi Zhang; Sudan Lin; Xuejun Bi; Shujuan Huang; Bo Jiang; Dong-Hoon Kim; How Yong Ng; Xueqing Shi (Chemical Engineering Journal, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Supercapacitor-isolated water electrolysis for renewable energy storage - Qian He; Hui Sun; Wen-Tao Bi; Xin-Yuan Wang; Bing Li; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2024)

Multi-kernel Learning Fusion Algorithm Based on RNN and GRU for ASD Diagnosis and Pathogenic Brain Region Extraction - Jie Chen; Huilian Zhang; Quan Zou; Bo Liao; Xia-an Bi (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Analysis of goat PPP6C mRNA profile, detection of genetic variations, and their associations with litter size - Yangyang Bai; Didi Bo; Yutian Bi; Ebadu Areb; Haijing Zhu; Chuanying Pan; Xianyong Lan (Animal Reproduction Science, 2024)

Numerical analysis on the wave attenuation characteristics of a suspended kelp farm - Guo-Hai Dong; Bo Zhang; Chun-Wei Bi (Ocean Engineering, 2024)

Differences in anodizing of two copper-containing coordination compounds by different degradation factors: Experiments and DFT calculations - Haodong Bi; Xu Zhao; Dandan Xu; Jianli Liu; Zhenglei He; Lihui An; Bo Zhu; Chang Sun; Zhengxin Li (Journal of Cleaner Production, 2024)

The transport of bismuth in HCl-bearing aqueous vapour and low-density aqueous supercritical fluids: Implications for natural systems - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Qi Liu; Fei-Xiang Liu; Yuan Mei; Zi-Qi Jiang; Lin-Bo Shang; Jing-Jing Zhu; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2024)

A review of distribution and functions of extracellular DNA in the environment and wastewater treatment systems - Shaopo Wang; Ruimin Tian; Yanmeng Bi; Fansheng Meng; Rui Zhang; Chenchen Wang; Dong Wang; Lingjie Liu; Bo Zhang (Chemosphere, 2024)

Characteristics of number concentration, size distribution and components of particulate matter emitted from a typical large civil airport - Sihan Yin; Zhichao Lu; Yufei Zhang; Lilai Song; Shenyu Bi; Xi Luo; Lu Yao; Xiaohui Bi; Han Bo; Yinchang Feng (Science of The Total Environment, 2024)

Late Triassic paleolatitude of the Southern Qiangtang terrane, central Tibet: Implications for the closure of the Longmu Co-Shuanghu Paleo-Tethyan Ocean - Xingduo Ma; Yalin Li; Xiaodong Tan; Shuai Li; Zijian Li; Jiawei Zhang; Wenjun Bi; Yongyong Jia; Bo Yang (Journal of Asian Earth Sciences, 2024)

Corrigendum to “Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports” [Atmospheric Research, 302 (2024), 107304] - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Deep Canonical Correlation Fusion Algorithm Based on Denoising Autoencoder for ASD Diagnosis and Pathogenic Brain Region Identification - Huilian Zhang; Jie Chen; Bo Liao; Fang-xiang Wu; Xia-an Bi (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Mitochondria-Related Gene MAOB is a Key Biomarker of Osteoarthritis and Inhibition of Its Expression Reduces LPS-induced Chondrocyte Damage - Shiqi Bi; Bo Han; Hongjuan Fan; Yongming Liu; Xuewen Cui (Biochemical Genetics, 2024)

Isolation of Rhizobacteria from Crocus Sativus L. Rhizosphere and Their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xue-Wen Bi; Jia-Hao Zhang; Zi-Hui Zhao; Khalid Rahman; Bo Zhu; Lu-Ping Qin; Ting Han (Journal of Plant Growth Regulation, 2024)

Zinc Ameliorates Tripterygium Glycosides–Induced Reproductive Impairment in Male Rats by Regulating Zinc Homeostasis and Expression of Oxidative Stress–Related Genes - Jing Ma; He Tan; Jiajie Bi; Bo Sun; Yingxian Zhen; Weiguang Lian; Shusong Wang (Biological Trace Element Research, 2024)

Efficient trimethoprim removal via cooperation of radical and non-radical pathways in UV/peroxymonosulfate: Kinetics, mechanisms and disinfection by-products-associated risks - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Juan Wang; Yu-Qiong Gao; Dong-Su Bi; Bo Wang; Xing-Yan Mu; Xiao-Jun Hu (Journal of Environmental Chemical Engineering, 2024)

Preservation and reactivation of anammox biomass: A mini review - Xiaoying Chen; Lingjie Liu; Yanmeng Bi; Fansheng Meng; Dong Wang; Chunsheng Qiu; Chenchen Wang; Shaopo Wang; Bo Zhang (Journal of Environmental Chemical Engineering, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Endothelial extracellular vesicles induce acute lung injury via follistatin-like protein 1 - Hao-Xiang Yuan; Ya-Ting Chen; Yu-Quan Li; Yan-Sheng Wang; Zhi-Jun Ou; Yan Li; Jian-Jun Gao; Meng-Jie Deng; Yuan-Kai Song; Li Fu; Hong-Bo Ci; Feng-Jun Chang; et al. (Science China Life Sciences, 2024)

Analysis of forestry management based on dynamic life cycle assessment of biogenic carbon: A case study of a forestry resource-based city in Northeast China - Bo Song; Jin Tang; Feng Long; Yuqing Peng; Fenfen Bi; Yueao Kang; Dayi Qian (Journal of Cleaner Production, 2024)

Mobility, bacterial hosts, and risks of antibiotic resistome in submicron bioaerosols from a full-scale wastewater treatment plant - Tang Yang; Xuyi Wang; Lu Jiang; Xiaoliang Hui; Xuejun Bi; Xiang Zheng; Bo Jiang; Xiaodong Wang (Journal of Environmental Management, 2024)

Improving enzyme accessibility in the aqueous enzymatic extraction process by microwave-induced porous cell walls to increase oil body and protein yields - Xin Guo; Bi-cong Wu; Yun Jiang; Yu Zhang; Bo Jiao; Qiang Wang (Food Hydrocolloids, 2024)

Antibiotic resistance genes associated with size-segregated bioaerosols from wastewater treatment plants: A review - Tang Yang; Xuyi Wang; Lu Jiang; Xin Sui; Xuejun Bi; Bo Jiang; Zhanpeng Zhang; Xinlong Li (Environmental Pollution, 2024)

Variation of runoff-sediment relationship at flood event scale in three typical watersheds of the Loess Plateau - Ren Geng; Zixuan Ye; Peng Tian; Qiu Jin; Bo Bi; Guangju Zhao; Xingmin Mu; Tongshun Wang; Dadong Zhu (CATENA, 2024)

Engineered PVA aerogels for effective mercury species removal with quick regeneration in wastewater remediation - Mimi Sun; Mengzhu Cao; Jingjuan Wang; Yanni Bi; Chong-Bo Ma (Journal of Water Process Engineering, 2024)

Innovations and challenges in the production of prepared dishes based on central kitchen engineering: A review and future perspectives - Yangyang Jia; Lanlan Hu; Ruifeng Liu; Wei Yang; Ibrahim Khalifa; Jicai Bi; Yunbo Li; Jianlong Zhen; Beiping Wang; Zhao Zhang; Erpeng Zhang; Bo Li (Innovative Food Science & Emerging Technologies, 2024)

Design, modeling and experiments of swing L-shape piezoelectric beam applied to tidal and wave energy harvesting - Bo Feng; Haiyang Xu; Bohan Wang; Yuankui Wang; Yuqin Zhu; Ran Bi; Dahai Zhang; Peng Qian (Ocean Engineering, 2023)

The predictive, preventive, and personalized medicine of insomnia: gut microbiota and inflammation - Hao-Wen Chen; Rui Zhou; Bi-Fei Cao; Kuan Liu; Qi Zhong; Yi-Ning Huang; Hua-Min Liu; Jin-Qing Zhao; Xian-Bo Wu (EPMA Journal, 2023)

Enhanced photocatalyst with TiO2-anchored iron tailings structure for highly efficient degradation of doxycycline hydrochloride - Bo Sun; Ziyin Guo; Feifan Ren; Xiaona Pan; Chunjuan Lyu; Xingxing Qiao; Wenlong Bi; Fenwu Liu; Qingjie Hou (Journal of Cleaner Production, 2023)

Recovery of carbon from spent carbon cathode by alkaline and acid leaching and thermal treatment and exploration of its application in lithium-ion batteries - Hao Zhou; Dayong Zhang; Yongjun Jiang; Bo Zeng; Chenxi Zhao; Mingjie Zhang; Baiyan Zeng; Xiaoquan Zhu; Xintai Su; Valentin Romanovski; Ran Bi (Environmental Science and Pollution Research, 2023)

Interfacial mechanism and inactivation efficiency of bacteriophage MS2 by ozone in high turbidity and algal-laden water resource - Lu Wang; Yi-bo Hu; Xiaochao Bi; V. Vasanthakumar; Zhiyong Zhang; Ming-Lai Fu; Wenjie Sun; Baoling Yuan (Journal of Water Process Engineering, 2023)

Efficient methotrexate adsorption on magnetic-functionalised UiO-66-NH2: Selectivity, mechanisms and recycling - Qiang Bi; Bo Yang; Kun Zhang; Tong Yang; Peng Wang; Long Shi; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Zinc Improves Semen Parameters in High-Fat Diet-Induced Male Rats by Regulating the Expression of LncRNA in Testis Tissue - Jing Ma; Jiajie Bi; Bo Sun; Huanhuan Li; Yuejia Li; Shusong Wang (Biological Trace Element Research, 2023)

Antibiotic resistome associated with inhalable bioaerosols from wastewater to atmosphere: Mobility, bacterial hosts, source contributions and resistome risk - Tang Yang; Xuyi Wang; Xiaoliang Hui; Lu Jiang; Xuejun Bi; How Yong Ng; Xiang Zheng; Shujuan Huang; Bo Jiang; Xiaolin Zhou (Water Research, 2023)

Mechanisms of damage to sperm structure in mice on the zinc-deficient diet - Bo Sun; Jing Ma; Junsheng Liu; Yuejia Li; Jiajie Bi; Liger Te; Xin Zuo; Shusong Wang (Journal of Trace Elements in Medicine and Biology, 2023)

Effects of TCPP and TCEP exposure on human corneal epithelial cells: Oxidative damage, cell cycle arrest, and pyroptosis - Zhen-Ning Zhang; Dan-Lei Yang; Hai Liu; Jue Bi; Ya-Bo Bao; Jiao-Yang Ma; Qin-Xiang Zheng; Dao-Lei Cui; Wei Chen; Ping Xiang (Chemosphere, 2023)

Determinants of trade of mineral resources between China and ASEAN - Bo Wang; Haoting Yang; Wenjuan Tian; Chunyu Bi (Resources Policy, 2023)

Green infrastructure and natural resource utilization for green development in selected belt and road initiative countries - Bo Wang; Haoting Yang; Chunyu Bi; Yanchao Feng (Resources Policy, 2023)

Evaluation of the respective contribution of anode and cathode for triclosan degradation in a bioelectrochemical system - Min-Hua Cui; Qian Zhang; John Justo Ambuchi; Lan-Ying Liu; Lei Chen; Shi-Ming Niu; Chao Zhang; Hong-Bo Liu; Chao Tie; Xue-Juan Bi; He Liu; Ai-Jie Wang (Bioresource Technology, 2023)

Study on the stability and disaster mechanism of layered soil slopes under heavy rain - Yang Li; Kaixi Xue; Yu Zhao; Chaolin Wang; Jing Bi; Tianyuan Wang; Shenfu Wang; Bo Zhang (Bulletin of Engineering Geology and the Environment, 2023)

Zinc-Deficient Diet Causes Imbalance in Zinc Homeostasis and Impaired Autophagy and Impairs Semen Quality in Mice - Bo Sun; Jing Ma; Liger Te; Xin Zuo; Junsheng Liu; Yuejia Li; Jiajie Bi; Shusong Wang (Biological Trace Element Research, 2023)

Pyridine N of N/Co-co-doped graphite gas diffusion electrode facilitating the efficient production of hydroxyl radicals in the electro-peroxone process - Qiang Bi; Sisi Jiang; Changfeng Hu; Li Zhang; Yilin Zhao; Bo Yang; Guoping Li; Juanqin Xue (Journal of Environmental Chemical Engineering, 2023)

Efficient removal of doxycycline using Schwertmannite as a heterogeneous Fenton-like catalyst over a wide pH range - Yu Tian; Fenwu Liu; Bo Sun; Zhenye Tong; Peng Fu; Jingzhi Zhang; Wenlong Bi; Shaozu Xu; Guangpeng Pei (Journal of Environmental Chemical Engineering, 2023)

Apatite and fluorite control the transport of tungsten in calcium-bearing hydrothermal fluids - Xin-Song Wang; A.E. Williams-Jones; Rui-Zhong Hu; Zi-Qi Jiang; Lin-Bo Shang; Xian-Wu Bi (Geochimica et Cosmochimica Acta, 2023)

A methodological framework for assessing pastoral socio-ecological system vulnerability: A case study of Altay Prefecture in Central Asia - Zihan Yang; Bo Li; Bo Nan; Xuhuan Dai; Chenchen Peng; Xu Bi (Science of The Total Environment, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Effect of biochars with different particle sizes on fates of antibiotics and antibiotic resistance genes during composting of swine manure - Zhenye Tong; Fenwu Liu; Bo Sun; Yu Tian; Jingzhi Zhang; Jiaze Duan; Wenlong Bi; Junmei Qin; Shaozu Xu (Bioresource Technology, 2023)

The accumulation of organic contaminants in hair with different biological characteristics - Bin Tang; Jing Zheng; Shi-Mao Xiong; Feng-Shan Cai; Min Li; Yan Ma; Bo Gao; Dong-Wei Du; Yun-Jiang Yu; Bi-Xian Mai (Chemosphere, 2023)

Quantifying biochar-induced greenhouse gases emission reduction effects in constructed wetlands and its heterogeneity: A multi-level meta-analysis - Bi-Ni Jiang; Min-Bo Lu; Zhi-Yong Zhang; Bo-Lun Xie; Hai-Liang Song (Science of The Total Environment, 2023)

Exploration of β-glucosidase-producing microorganisms community structure and key communities driving cellulose degradation during composting of pure corn straw by multi-interaction analysis - Yue Han; Wanying Liu; Nuo Chang; Lei Sun; Ayodeji Bello; Liting Deng; Liyan Zhao; Ugochi Uzoamaka Egbeagu; Bo Wang; Yan Zhao; Mingming Zhao; Ruixin Bi; et al. (Journal of Environmental Management, 2023)

Hydrothermal carbonization of alfalfa: role of processing variables on hydrochar properties - Jun Zhou; Mingjie Yu; Jianhua Qu; Modupe Sarah Akindolie; Fuxuan Bi; Yang Liu; Zhao Jiang; Lei Wang; Bo Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Spatial-temporal distributions and influential factors of phthalate acid esters in sediments of three lakes in Inner Mongolia - Yan Ma; Tong Liu; Bo-Tao Zhang; Yan Liu; Peng Shao; Chen Sun; Yichen Zhang; Jiale Bi; Yunkai Dong; Shengrui Wang; Guoming Zhang (Environmental Science and Pollution Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Estimate greenhouse gas emissions from water-saving and drought-resistance rice paddies by deNitrification-deComposition model - Xianxian Zhang; Huifeng Sun; Junguo Bi; Bo Yang; Jining Zhang; Cong Wang; Sheng Zhou (Clean Technologies and Environmental Policy, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Screening of reference genes in tiger puffer (Takifugu rubripes) across tissues and under different nutritional conditions - Zhangbin Liao; Zhiyuan Sun; Qingzhu Bi; Qingli Gong; Bo Sun; Yuliang Wei; Mengqing Liang; Houguo Xu (Fish Physiology and Biochemistry, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Arbuscular mycorrhizal colonization rate of an exotic plant, Galinsoga quadriradiata, in mountain ranges changes with altitude - Gang Liu; Rui-Ling Liu; Wen-Gang Zhang; Ying-Bo Yang; Xiao-Qiong Bi; Ming-Zhu Li; Xiao-Yan Chen; Hua Nie; Zhi-Hong Zhu (Mycorrhiza, 2021)

Serological characteristics of COVID-19 patients - Mi Zhou; Jing Zhong; Lei Bi; Pengcheng Shang; Yan Xing; Bo Wang; Jianlan He; Ying Xu; Tao Luo; Maohua Ma; Qingfeng Li (Infectious Diseases, 2020)

Alpinia oxyphylla–Schisandra chinensis Herb Pair Alleviates Amyloid-β Induced Cognitive Deficits via PI3K/Akt/Gsk-3β/CREB Pathway - Yu Qi; Huiting Jing; Xinhui Cheng; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (NeuroMolecular Medicine, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

MPTP-Induced Impairment of Cardiovascular Function - Xiaoli Liu; Bo Wei; Qianqian Bi; Qihang Sun; Li Li; Jian He; Yuancheng Weng; Shenyan Zhang; Genxiang Mao; Yizhong Bao; Shu Wan; Xiao Z. Shen; et al. (Neurotoxicity Research, 2020)

Combination of schisandrin and nootkatone exerts neuroprotective effect in Alzheimer’s disease mice model - Yu Qi; Xinhui Cheng; Huiting Jing; Tingxu Yan; Feng Xiao; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Rapid identification of a candidate nicosulfuron sensitivity gene (Nss) in maize (Zea mays L.) via combining bulked segregant analysis and RNA-seq - Xiaomin Liu; Bo Bi; Xian Xu; Binghua Li; Shengmin Tian; Jianping Wang; Hui Zhang; Guiqi Wang; Yujun Han; J. Scott McElroy (Theoretical and Applied Genetics, 2019)

Intracerebroventricular injection of resveratrol ameliorated Aβ-induced learning and cognitive decline in mice - Yu Qi; Lei Shang; Zhengzheng Liao; Hang Su; Huiting Jing; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2019)

Comparative Transcriptome Analysis of Rhizoctonia solani-resistant and -Susceptible Rice Cultivars Reveals the Importance of Pathogen Recognition and Active Immune Responses in Host Resistance - Zhengjie Yuan; Yu Zhang; Guojuan Xu; Dongling Bi; Haiyan Qu; Xiaowei Zou; Xiaoqing Gao; Haihe Yang; Haiyan He; Xuli Wang; Jiandong Bao; Shimin Zuo; et al. (Journal of Plant Biology, 2018)

Neuroprotective effects of nootkatone from Alpiniae oxyphyllae Fructus against amyloid-β-induced cognitive impairment - Bosai He; Fanxing Xu; Feng Xiao; Tingxu Yan; Bo Wu; Kaishun Bi; Ying Jia (Metabolic Brain Disease, 2018)

New phenanthrene and 9, 10-dihydrophenanthrene derivatives from the stems of Dendrobium officinale with their cytotoxic activities - Gui-Yun Zhao; Bo-Wen Deng; Chong-Yu Zhang; Yi-Da Cui; Jia-Yi Bi; Guo-Gang Zhang (Journal of Natural Medicines, 2018)

Reverse-time migration and amplitude correction in the angle-domain based on Poynting vector - Ji-Cheng Liu; Xiao-Bi Xie; Bo Chen (Applied Geophysics, 2017)

Erratum to: Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Haploinsufficiency of the E3 ubiquitin-protein ligase gene TRIP12 causes intellectual disability with or without autism spectrum disorders, speech delay, and dysmorphic features - Jing Zhang; Tomasz Gambin; Bo Yuan; Przemyslaw Szafranski; Jill A. Rosenfeld; Mohammed Al Balwi; Abdulrahman Alswaid; Lihadh Al-Gazali; Aisha M. Al Shamsi; Makanko Komara; Bassam R. Ali; Elizabeth Roeder; et al. (Human Genetics, 2017)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Broadband seismic illumination and resolution analyses based on staining algorithm - Bo Chen; Xiao-Feng Jia; Xiao-Bi Xie (Applied Geophysics, 2016)

Soil concentration profiles and diffusion and emission of nitrous oxide influenced by the application of biochar in a rice-wheat annual rotation system - Ziqiang Zhou; Xin Xu; Zhichao Bi; Lu Li; Bo Li; Zhengqin Xiong (Environmental Science and Pollution Research, 2016)

Disruption of thalamic connectivity in Alzheimer’s disease: a diffusion tensor imaging study - Qing-Yong Zhu; Si-Wei Bi; Xiu-Ting Yao; Zhi-Yan Ni; Ying Li; Bo-Yu Chen; Guo-Guang Fan; Xiu-Li Shang (Metabolic Brain Disease, 2015)

Bioaccumulative characteristics of tetrabromobisphenol A and hexabromocyclododecanes in multi-tissues of prey and predator fish from an e-waste site, South China - Bin Tang; Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bi-Xian Mai (Environmental Science and Pollution Research, 2015)

Characterization of the hypoxia-inducible factor 1 alpha gene in the sperm whale, beluga whale, and Yangtze finless porpoise - Jianling Bi; Bo Hu; Jinsong Zheng; Jingzhen Wang; Wuhan Xiao; Ding Wang (Marine Biology, 2015)

Combining Bone Marrow Stromal Cells with Green Tea Polyphenols Attenuates the Blood-Spinal Cord Barrier Permeability in Rats with Compression Spinal Cord Injury - De-shui Yu; Li-bo Liu; Yang Cao; Yan-song Wang; Yun-long Bi; Zi-jian Wei; Song-ming Tong; Gang Lv; Xi-fan Mei (Journal of Molecular Neuroscience, 2015)

Clinical assessment and polysomnographic study of sleep apnea in a Chinese population of snorers - Chuan Shao; Jing-bo Jiang; Hong-cheng Wu; Shi-bo Wu; Bi-yun Yu; Yao-dong Tang (Journal of Zhejiang University-SCIENCE B, 2015)

Myosin II regulates actin rearrangement-related structural synaptic plasticity during conditioned taste aversion memory extinction - Ai-Ling Bi; Yue Wang; Shuang Zhang; Bo-Qin Li; Zong-Peng Sun; Hong-Sheng Bi; Zhe-Yu Chen (Brain Structure and Function, 2015)

Land subsidence in the modern Yellow River Delta based on InSAR time series analysis - Jin-Zhi Zhang; Hai-jun Huang; Hai-bo Bi (Natural Hazards, 2015)

Developing microsatellite markers for Geodorum eulophioides (Orchidaceae) and cross-species amplification in two sympatric, congeneric species - Ting Ying; Qi-Fang Geng; Dan-Bi Wang; Hong Liu; Jing Xu; Zi-Bing Zhang; Zhong-Sheng Wang; Yi-Bo Luo (Conservation Genetics Resources, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Species-Specific Bioaccumulation of Halogenated Organic Pollutants and Their Metabolites in Fish Serum from an E-Waste Site, South China - Yan-Hong Zeng; Xiao-Jun Luo; Xiao-Bo Zheng; Bin Tang; Jiang-Ping Wu; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2014)

Regulatory mechanism of ZNF139 in multi-drug resistance of gastric cancer cells - Yong Li; Bi-bo Tan; Qun Zhao; Li-qiao Fan; Yü Liu; Dong Wang (Molecular Biology Reports, 2014)

RNA-seq methods for identifying differentially expressed gene in human pancreatic islet cells treated with pro-inflammatory cytokines - Bo Li; Chang Long Bi; Ning Lang; Yu Ze Li; Chao Xu; Ying Qi Zhang; Ai Xia Zhai; Zhi Feng Cheng (Molecular Biology Reports, 2014)

Cloning and functional analysis of the flowering gene GmSOC1-like, a putative SUPPRESSOR OF OVEREXPRESSION CO1/AGAMOUS-LIKE 20 (SOC1/AGL20) ortholog in soybean - Xiaofan Na; Bo Jian; Weiwei Yao; Cunxiang Wu; Wensheng Hou; Bingjun Jiang; Yurong Bi; Tianfu Han (Plant Cell Reports, 2013)

Exon 47 skipping of fibrillin-1 leads preferentially to cardiovascular defects in patients with thoracic aortic aneurysms and dissections - Wen-Jing Wang; Peili Han; Jun Zheng; Fang-Yuan Hu; Yun Zhu; Jin-Sheng Xie; Jian Guo; Zhe Zhang; Jie Dong; Gu-Yan Zheng; Huiqing Cao; Tian-Shu Liu; et al. (Journal of Molecular Medicine, 2013)

Angelica sinensis (Oliv.) Diels in China: distribution, cultivation, utilization and variation - Hong Yi Zhang; Wen Gang Bi; Yi Yu; Wen Bo Liao (Genetic Resources and Crop Evolution, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Large-scale analysis of phosphorylated proteins in maize leaf - Ying-Dong Bi; Hong-Xia Wang; Tian-Cong Lu; Xiao-hui Li; Zhuo Shen; Yi-Bo Chen; Bai-Chen Wang (Planta, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Deletion analysis of SMN1 and NAIP genes in southern Chinese children with spinal muscular atrophy - Yu-hua Liang; Xiao-ling Chen; Zhong-sheng Yu; Chun-yue Chen; Sheng Bi; Lian-gen Mao; Bo-lin Zhou; Xian-ning Zhang (Journal of Zhejiang University-SCIENCE B, 2009)

Edaravone neuroprotection effected by suppressing the gene expression of the Fas signal pathway following transient focal ischemia in rats - Bo Xiao; Fang -Fang Bi; Yue -Qiang Hu; Fa -Fa Tian; Zhi -Guo Wu; Hadi M. Mujlli; Ling Ding; Xin -Fu Zhou (Neurotoxicity Research, 2007)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

Study on energy transfer between carotenoid and chlorophyll a in cytochrome b 6 f complex from Bryopsis corticulans - Bin-Xing Li; Ping Zuo; Xiao-Bo Chen; Liang-Bi Li; Jian-Ping Zhang; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2006)